Discontinuing operations - International Accounting Standards Committee; International Accounting Standards Committee (London : International Accounting Standards Committee, 1998)
Addresses presentation and disclosures relating to discontinuing operations.
"June 1998"--Cover.
oif 31/03/15
Loan
Keywords: Write-offs.; Accounting -- Standards